2010
DOI: 10.1371/journal.pone.0011466
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cancer Effect of HIV-1 Viral Protein R on Doxorubicin Resistant Neuroblastoma

Abstract: Several unique biological features of HIV-1 Vpr make it a potentially powerful agent for anti-cancer therapy. First, Vpr inhibits cell proliferation by induction of cell cycle G2 arrest. Second, it induces apoptosis through multiple mechanisms, which could be significant as it may be able to overcome apoptotic resistance exhibited by many cancerous cells, and, finally, Vpr selectively kills fast growing cells in a p53-independent manner. To demonstrate the potential utility of Vpr as an anti-cancer agent, we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…1A ). Although we have focused on the effects of Tat as an example of how HIV proteins might dysregulate cell cycle activation and trigger neurotoxicity, we recognize that other HIV proteins such as nef, vif, and vpr might also dysregulate CDKs [117, 118]. …”
Section: Resultsmentioning
confidence: 99%
“…1A ). Although we have focused on the effects of Tat as an example of how HIV proteins might dysregulate cell cycle activation and trigger neurotoxicity, we recognize that other HIV proteins such as nef, vif, and vpr might also dysregulate CDKs [117, 118]. …”
Section: Resultsmentioning
confidence: 99%
“…Blockage of NF-κB signaling can delay mitotic entry and keep cells at the G2 phase (40). Based on previous studies, protein phosphatase 2A (PP2A), a serine/threonine phosphatase, could play an essential role in G2 cell cycle arrest induced by Vpr (15,41). PP2A can dephosphorylate and modulate the activity of IKKβ (42), one of two catalytic subunits of IKK.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of Vpr protein was able to induce cell cycle arrest and apoptosis. Therefore, many studies have analyzed the potential antitumor activity of this molecule both in vitro and in vivo (7)(8)(9)(10)(11)(12)(13)(14)(15). Previous studies have shown that the Vpr protein appears to preferentially inhibit the growth of rapidly dividing tumor cells, but does not affect the normal cells regardless of changes in p53 expression (7)(8)(9)15 Abbreviations: Ad, adenovirus; GFP, green fluorescent protein; Vpr, viral protein R; MOI, multiplicity of infection; MTT, 3-(4,5)-dimethylthiazo(-2-yl)-2,5-di-phenyltetrazolium bromide; PI, propidium iodide; NF-κB, nuclear factor-κB…”
mentioning
confidence: 99%
“…The Adenoviral (Adv) Vpr construct was generated in this laboratory 16,17 by using the AdEasy Adenoviral Vector system (Cat#: 240009;…”
Section: Adenoviral Constructs and Cell Transductionmentioning
confidence: 99%